2016
DOI: 10.1016/j.rbre.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection in patients with juvenile idiopathic arthritis: factors associated with a good response

Abstract: In our study, more than half of the joints showed a good response to IIC. Younger patients at diagnosis and uveitis during the course of the disease had good response to IIC. Knees, wrists and elbows were the joints that best responded to IIC. IIC proved to be a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This is particularly pertinent given the often‐delayed onset of psoriatic features in children previously classified as oligo or polyarticular JIA 36 . That younger age of disease onset is generally associated with better outcomes, in terms of disease activity including treatment response, 37–39 is readily corroborated. However, the association is not as clear after adjustment for ILAR category, because those with oligoarthritis tend to both be younger and have milder disease 40 .…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly pertinent given the often‐delayed onset of psoriatic features in children previously classified as oligo or polyarticular JIA 36 . That younger age of disease onset is generally associated with better outcomes, in terms of disease activity including treatment response, 37–39 is readily corroborated. However, the association is not as clear after adjustment for ILAR category, because those with oligoarthritis tend to both be younger and have milder disease 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that more than half of the joints showed a good response to IACIs, and those with uveitis responded well to IACIs during the disease. Knees, wrists, and elbows were the most effective joints for IACIs ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…IACIs appeared to be a safe and effective treatment option for the management of JIA, particularly the management of oligoarticular JIA. 40,41 IACIs are an effective way to control disease activity and to induce resolution of synovitis, decrease the presence of joint and limb deformities, improve function, provide pain relief and serve as A systematic review to evaluate the advantages of administering CSs during arthrocentesis for temporomandibular disorders, including JIA, found no significant differences in the clinical outcomes observed between the CS injection group and the control groups (which were injected with normal saline, physiological salt water or Ringer's lactate). 43 Ravelli et al 44…”
Section: Intra-articular Corticosteroidsmentioning
confidence: 99%